2019
DOI: 10.1371/journal.pmed.1002975
|View full text |Cite
|
Sign up to set email alerts
|

Current situation and progress toward the 2030 health-related Sustainable Development Goals in China: A systematic analysis

Abstract: BackgroundThe Sustainable Development Goals (SDGs), adopted by all United Nations (UN) member states in 2015, established a set of bold and ambitious health-related targets to achieve by 2030. Understanding China’s progress toward these targets is critical to improving population health for its 1.4 billion people.Methods and findingsWe used estimates from the Global Burden of Disease (GBD) Study 2016, national surveys and surveillance data from China, and qualitative data. Twenty-eight of the 37 indicators inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…The current study is part of a largescale project assessing the progress of China in achieving health-related SDGs, and which has published detailed methods on the qualitative data collection and analysis and the projection model. 14…”
Section: Approachmentioning
confidence: 99%
“…The current study is part of a largescale project assessing the progress of China in achieving health-related SDGs, and which has published detailed methods on the qualitative data collection and analysis and the projection model. 14…”
Section: Approachmentioning
confidence: 99%
“…It is found that men are more active than women in the East and South-East Asia. 22 Young people and children get health benefits through physical activity. A comprehensive education system combined sport and physical activities with the school curriculum for healthy learning.…”
Section: Goal 4: Ensure Equal and Affordable Schooling For All And Prmentioning
confidence: 99%
“…However, the achievement index of the family planning needs does not meet the modern contraception methods, which is expected to reach 76.6 by 2030 because of the unmet needs of single mating women. 22 In recent decades, children's undernutrition has significantly improved, while overweight and obesity in China have emerged as a new threat to public health. The stunting rate decreased from 16.3% to 8.1% for children aged 6 and under and wasting decreased from 2.6% to 2.0% for the years 2002 to 2013.…”
Section: China's Progress Towards Healthy China Under Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ignores those who seek treatment but fall into poverty as a result of expenditure. However, this kind of poverty-related lack of proper care is still a challenge in China and to eliminate infectious diseases among the poor and improve their accessibility and affordability with respect to disease prevention, treatment and rehabilitation services will take more time [25]. For example, the results from three rounds of a national survey of important parasitic diseases showed that with the economic development, the average prevalence rate of soil-transmitted helminthiasis dropped from 59.8% in 1991 to 19.6% in 2003, and continued down to 4.8% in 2013 [9].…”
Section: Poverty Leads To Illnessmentioning
confidence: 99%